2015
DOI: 10.1038/ncomms7863
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of EPAS1 variant in cattle with high-altitude pulmonary hypertension

Abstract: High-altitude pulmonary hypertension (HAPH) has heritable features and is a major cause of death in cattle in the Rocky Mountains, USA. Although multiple genes are likely involved in the genesis of HAPH, to date no major gene variant has been identified. Using whole-exome sequencing, we report the high association of an EPAS1 (HIF2α) double variant in the oxygen degradation domain of EPAS1 in Angus cattle with HAPH, mean pulmonary artery pressure >50 mm Hg in two independent herds. Expression analysis shows up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 24 publications
2
73
2
3
Order By: Relevance
“…Comparison between cattle that developed PH at altitude and those that did not revealed variants in EPAS1 that likely confer gain of function and were associated with HPH susceptibility. 113 Taken together, the genomic studies in both humans and cattle at high altitude independently identified variants in the HIF signaling pathway that confer protection or susceptibility to high-altitude PH.…”
Section: Mechanisms Of Hph: Lessons From High-altitude Genomicsmentioning
confidence: 99%
“…Comparison between cattle that developed PH at altitude and those that did not revealed variants in EPAS1 that likely confer gain of function and were associated with HPH susceptibility. 113 Taken together, the genomic studies in both humans and cattle at high altitude independently identified variants in the HIF signaling pathway that confer protection or susceptibility to high-altitude PH.…”
Section: Mechanisms Of Hph: Lessons From High-altitude Genomicsmentioning
confidence: 99%
“…Our initial filtering strategy did not show a single genetic variant, although we (15,18,19,43). In this context, given the possibility that multiple genes are required to develop some disease phenotypes, we hypothesize that IPAH may develop due to either (1) multiple GVs in certain key pathways, or (2) multiple affected key pathways within an individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have previously been identified in Tibetan people, and have been shown to help humans adapt to high altitude conditions [24][25][26][27] , hypoxia, and myocardial infarction [28] . Previous studies of these genes in local domestic livestock were performed either solely within cattle [29] or Yak. In total, 44 SNVs were found in the CDS region of these four genes, including 16 non-synonymous SNVs.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, a SNV in EPAS1 has been detected between Tibetan (high-altitude) and Han (low-altitude) populations, and is associated with erythrocyte abundance, and thus supports the role of EPAS1 in the adaptation to hypoxia necessary for adaptation to high altitudes [24] . Newman et al [29] found a high degree of association in the oxygen degradation domain of EPAS1 between an EPAS1 (HIF-2α) double variant in Angus cattle with high-altitude pulmonary hypertension (HAPH) and demonstrated that the variant appears to be prevalent only in lowland cattle. In Yak, three novel SNPs have also been identified in EPAS1, and have been genotyped in three breeds.…”
Section: Discussionmentioning
confidence: 99%